2017
DOI: 10.1200/jco.2016.70.1474
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Palliative Care Into Standard Oncology Care: American Society of Clinical Oncology Clinical Practice Guideline Update

Abstract: Purpose To provide evidence-based recommendations to oncology clinicians, patients, family and friend caregivers, and palliative care specialists to update the 2012 American Society of Clinical Oncology (ASCO) provisional clinical opinion (PCO) on the integration of palliative care into standard oncology care for all patients diagnosed with cancer. Methods ASCO convened an Expert Panel of members of the ASCO Ad Hoc Palliative Care Expert Panel to develop an update. The 2012 PCO was based on a review of a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
1,295
1
79

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,668 publications
(1,402 citation statements)
references
References 67 publications
27
1,295
1
79
Order By: Relevance
“…32 Integrating early enhanced supportive care for people with advanced cancer into standard oncology care has been recommended by the American Society of Clinical Oncology, which, after conducting a systematic review of clinical trials concluded there is strong evidence that early palliative care improves quality of life, reduces depression and improves satisfaction with care; however, there was less evidence to show that it improves survival. 33 Integrated palliative care and oncology services vary by hospital in the UK as no national guidance exists. This integration is arguably a more cost-efficient use of resources than approving use of some of the systemic targeted treatments as not a single trial of enhanced supportive care has demonstrated a cost increase over routine care.…”
Section: Supportive and Palliative Carementioning
confidence: 99%
“…32 Integrating early enhanced supportive care for people with advanced cancer into standard oncology care has been recommended by the American Society of Clinical Oncology, which, after conducting a systematic review of clinical trials concluded there is strong evidence that early palliative care improves quality of life, reduces depression and improves satisfaction with care; however, there was less evidence to show that it improves survival. 33 Integrated palliative care and oncology services vary by hospital in the UK as no national guidance exists. This integration is arguably a more cost-efficient use of resources than approving use of some of the systemic targeted treatments as not a single trial of enhanced supportive care has demonstrated a cost increase over routine care.…”
Section: Supportive and Palliative Carementioning
confidence: 99%
“…3,[11][12][13][14][15][16] Palliative care should be initiated by the primary oncology team (including physicians, nurses, social workers, mental health professionals, chaplains, physician assistants, pharmacists, and dietitians) and then augmented via collaboration with an interdisciplinary team of palliative care experts to address intractable symptoms and/or complex psychosocial issues. When further anticancer therapy is unlikely to provide additional benefit or is expected do more harm than good, palliative care becomes the predominant care offered to patients with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Mrs. X was treated within the French Health care system. However the disease progressed and the patient entered a phase of purely palliative treatment, which corresponded to current guidelines [20]. Difficulties were encountered due to the patient's status as an illegal immigrant, her poverty, absence of supportive family structure, and non-European culture.…”
Section: Resultsmentioning
confidence: 99%